Linking farmer and beekeeper preferences with ecological knowledge to improve crop pollination. Issue 4 (29th October 2019) - Breeze, Tom D.; Boreux, Virginie; Cole, Lorna; Dicks, Lynn; Klein, Alexandra‐Maria; Pufal, Gesine; Balzan, Mario V.; Bevk, Danilo; Bortolotti, Laura; Petanidou, Theodora; Mand, Marika; Pinto, M. Alice; et al.
Abstract: Pollination by insects is a key input into many crops, with managed honeybees often being hired to support pollination services. Despite substantial research into pollination management, no European studies have yet explored how and why farmers managed pollination services and few have explored why beekeepers use certain crops. Using paired surveys of beekeepers and farmers in 10 European countries, this study examines beekeeper and farmer perceptions and motivations surrounding crop pollination. Almost half of the farmers surveyed believed they had pollination service deficits in one or more of their crops. Less than a third of farmers hired managed pollinators; however, most undertook at least one form of agri‐environment management known to benefit pollinators, although few did so to promote pollinators. Beekeepers were ambivalent towards many mass‐flowering crops, with some beekeepers using crops for their honey that other beekeepers avoid because of perceived pesticide risks. The findings highlight a number of largely overlooked knowledge gaps that will affect knowledge exchange and co‐operation between the two groups. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. Foreign Language Abstract 摘要: 昆虫授粉是多种作物的重要获粉途径, 蜜蜂则常被用来协助授粉服务。尽管存在大量授粉管理调研, 欧洲目前尚无任何研究显示农民管理授粉服务的方式及原因, 仅少量研究表明养蜂人使用某些特定作物的原因。 在欧洲10国针对养蜂人和农民配对调查, 此项研究以考察养蜂人和农民围绕作物授粉的认知和动机。 近半数针对农民的调查显示, 其某种或多种作物存在授粉服务不足现象。 三分之一以下农民雇佣传粉管理服务, 尽管多数传粉服务使用至少一种已知能为传粉者受益的农田环境管理项目, 但仅少数以增加传粉者为目的。 养蜂人对许多大量开花作物持矛盾态度, 一些养蜂人使用这些作物提取蜂蜜, 另一些则因农药风险性而敬而远之。 调查结果突显出许多被大程度忽视的知识缺口, 将影响农民与养蜂人间的知识交流及协作。 Riassunto: L'impollinazione da parte degli insetti è un fattore chiave in molte colture agricole e le api mellifere sono spesso impiegate per il servizio di impollinazione. Nonostante le approfondite ricerche sulla gestione dell'impollinazione, nessuno studio europeo ha ancora esplorato come e perché gli agricoltori utilizzano il servizio di impollinazione e il motivo per cui gli apicoltori sfruttano determinate colture per produrre miele. Utilizzando sondaggi paralleli rivolti ad apicoltori e agricoltori in 10 paesi europei, questo studio ha analizzato le percezioni e le motivazioni di apicoltori e agricoltori relativamente all'impollinazione delle colture. Quasi la metà degli agricoltori intervistati riteneva di avere un deficit del servizio di impollinazione in una o più delle loro colture. Pochi agricoltori hanno dichiarato di impiegare impollinatori allevati, tuttavia la maggior parte di loro ha intrapreso almeno una qualche forma di misura agroambientale volta favorire gli impollinatori, sebbene pochi lo facessero con l'espressa finalità di sostenere gli impollinatori. Le risposte degli apicoltori sono risultate ambivalenti riguardo a molte colture agricole: alcuni di loro le utilizzano per produrre miele, altri le evitano a causa dei rischi da pesticidi. I risultati rilevano numerose opportunità per un'ulteriore collaborazione tra agricoltori e apicoltori e diverse lacune di conoscenza che devono essere colmate. Zusammenfassung: Bestäubung durch Insekten ist essentiell für viele Feldfrüchte, wobei immer wieder gezüchtete Honigbienen gemietet werden um Bestäubungsdienste in der Landwirtschaft zu unterstützen. Obwohl erheblicher Forschungsaufwand in das Bestäubungsmanagement geflossen ist, gibt es keine europäischen Studien die untersuchen, wie und warum Landwirte Bestäubungsdienste nutzen und nur wenige Studien erforschten warum Imker bestimmte Feldfrüchte für ihre Bienen bevorzugen. Durch das Einsetzen gleichzeitiger Umfragen unter Imkern und Landwirten in zehn europäischen Ländern untersuchte diese Studie die Präferenzen und Motivationen von Landwirten und Imkern im Bezug auf die Nutzpflanzenbestäubung in der Landwirtschaft. Fast die Hälfte der teilnehmenden Landwirte gaben an, dass sie einen Bestäubungsdefizit bei einem oder mehreren ihrer Anbauprodukte haben. Weniger als ein Drittel der Landwirte mieteten Honigbienen oder andere bestäubende Bienen, aber die meisten führten mindestens eine Agrarumweltmaßnahme durch, die nachweislich Bestäuber fördert. Allerdings taten dies nur wenige um direkt Bestäuber zu fördern. Imker waren zwiespältig im Bezug auf Feldfrüchte mit Massentrachten wie z.B. Raps – einige Imker nutzen bestimmte Anbauprodukte mit Massentrachten zur Honigproduktion, während andere genau dies selbe Tracht aufgrund von angenommener Pestizidbelastung vermieden. Diese Erkenntnisse identifizieren verschiedene Möglichkeiten für weitere Kollaborationen zwischen Landwirten und Imkern sowie die Wissenslücken die geschlossen werden müssen. περίληψη: Η επικονίαση με έντομα αποτελεί κλειδί για πολλές καλλιέργειες, η επικονίαση των οποίων συχνά υποστηρίζεται από εκμισθωμένες κοινές μέλισσες. Παρά τη σημαντική έρευνα που έχει υλοποιηθεί σχετικά με την διαχείριση της επικονίασης, καμία Ευρωπαϊκή έρευνα δεν έχει εξετάσει το πώς και γιατί οι γεωργοί διαχειρίζονται τις υπηρεσίες επικονίασης, ενώ ελάχιστες μελέτες έχουν διεξαχθεί για τους λόγους χρήσης συγκεκριμένων καλλιεργειών από τους μελισσοκόμους. Συλλέγοντας δεδομένα μέσω παράλληλων ερωτηματολογίων από μελισσοκόμους και γεωργούς σε 10 Ευρωπαϊκές χώρες, η παρούσα έρευνα εξετάζει τις αντιλήψεις μελισσοκόμων και γεωργών, καθώς και τα κίνητρά τους σχετικά με την επικονίαση των καλλιεργειών. Σχεδόν οι μισοί από τους ερωτώμενους γεωργούς δήλωσαν ότι θεωρούν ως μη ικανοποιητική ή ελλιπή την επικονίαση σε μία ή περισσότερες καλλιέργειες τους. Οι γεωργοί που χρησιμοποιούν επικονιαστές υπό διαχείριση δεν ξεπερνούν το ένα τρίτο των ερωτωμένων. Οι περισσότεροι όμως φέρονται να έχουν υιοθετήσει τουλάχιστον μια μορφή αγρο‐περιβαλλοντικής διαχείρισης που ευνοεί τους επικονιαστές, αν και λίγοι την εφαρμόζουν με σκοπό την ενίσχυση των τελευταίων. Οι μελισσοκόμοι είχαν αντιτιθέμενες απόψεις σχετικά με πολλές καλλιέργειας μαζικής ανθοφορίας, με κάποιους από αυτούς να χρησιμοποιούν μελιτοφόρες καλλιέργειες οι οποίες αποφεύγονται από άλλους εξαιτίας δυνητικών κινδύνων από φυτοφάρμακα. Τα αποτελέσματα της έρευνας αναδεικνύουν αρκετές ευκαιρίες για περαιτέρω συνεργασία μεταξύ γεωργών και μελισσοκόμων, καθώς και σημαντικά κενά γνώσης που απαιτούν επίλυση. Resumo: A polinização entomófila é um fator de produção chave em muitas culturas pelo que na agricultura são frequentemente contratadas colónias para apoiar os serviços de polinização. Apesar da intensa investigação sobre a gestão da polinização, nenhum estudo europeu analisou "como" e "por que" razão os agricultores gerem a polinização e poucos exploraram, até agora, as razões pelas quais os apicultores usam certas culturas agrícolas. Este estudo examina as percepções e motivações dos agricultores e apicultores em torno da questão da polinização das culturas, a partir da informação extraída de inquéritos simultâneos a apicultores e agricultores implementados em 10 países europeus. Cerca de metade dos agricultores inquiridos acredita haver déficits nos serviços de polinização em uma ou mais das suas culturas. Menos de um terço dos agricultores contrata serviços de polinização. No entanto, a maioria tem vindo a implementar pelo menos uma medida de gestão agro‐ambiental conhecida por beneficiar polinizadores, embora poucos agricultores tenham feito alguma coisa para os promover. Os apicultores são ambivalentes em relação a muitas culturas; as culturas que são utilizadas por alguns apicultores para a produção de mel são evitadas por outros devido aos riscos percepcionados dos pesticidas. Os resultados deste estudo identificam várias oportunidades para uma maior colaboração entre agricultores e apicultores e ao mesmo tempo as lacunas de conhecimento que precisam de ser resolvidas. Résumé: La pollinisation par les insectes est un intrant majeur dans de nombreuses cultures, les abeilles mellifères étant souvent utilisées pour soutenir les services de pollinisation. Malgré des recherches approfondies sur la gestion de la pollinisation, aucune étude européenne n'a encore exploré comment et pourquoi les agriculteurs gèrent les services de pollinisations, et peu se sont penchées sur les raisons pour lesquelles les apiculteurs choisissent certaines cultures plutôt que d'autres. Cette étude examine les perceptions ainsi que les motivations des apiculteurs et des agriculteurs sur le thème de la pollinisation des cultures, en utilisant des enquêtes couplées auprès d'apiculteurs et d'agriculteurs dans 10 pays européens. Près de la moitié des agriculteurs interrogés estimaient qu'une ou plusieurs de leurs cultures était en déficit de pollinisation. Moins d'un tiers des agriculteurs louaient des pollinisateurs domestiques, mais la plupart mettait en œuvre au moins une forme de gestion agro‐environnementale connue pour être bénéfique aux pollinisateurs, bien que peu l'aient fait pour promouvoir les pollinisateurs. Les apiculteurs étaient partagés sur beaucoup de cultures à floraison massive. Certains apiculteurs utilisaient ces cultures pour leur production de miel quand d'autres les évitaient en raison des risques perçus associés aux pesticides. Les résultats mettent en lumière un certain nombre de lacunes largement négligées qui auront une incidence sur l'échange de connaissances et la coopération entre les deux groupes. Aпcтpaкт: Oпpaшивaњe инceктимa je кљyчнo yлaгaњe y мнoгe гajeнe биљкe, чecтo ce мeдoнocнe пчeлe кopиcтe зa пpyжaњe ycлyгe oпpaшивaњa. Упpкoc знaчajним иcтpaживaњимa y вeзи ca oпpaшивaњeм, joш yвeк нeмa eвpoпcкиx cтyдиja кoje cy ce бaвилe иcтpaживaњeм кaкo и зaштo cy пoљoпpивpeдници кopиcтили oпpaшивaчкe ycлyгe, a мaлo je и oниx кojи cy иcтpaживaли зaштo пчeлapи кopиcтe бaш oдpeђeнe yceвe. Упapивaњeм yпитникa зa пчeлape и пoљoпpивpeдникe y 10 eвpoпcкиx зeмaљa, oвa cтyдиja иcпитyje oпaжaњa и мoтивaциjy пчeлapa и пoљoпpивpeдникa y вeзи ca oпpaшивaњeм yceвa. Гoтoвo пoлoвинa aнкeтиpaниx пoљoпpивpeдникa вepoвaли cy дa пocтojи нeдocтaтaк ycлyгe oпpaшивaњa кoд jeднe или вишe њиxoвиx гajeниx биљaкa. Maњe oд тpeћинe пoљoпpивpeдникa cy кopиcтили yзгajaнe oпpaшивaчe, мeђyтим вeћинa je пpeyзeлa бapeм jeдaн нaчин yпpaвљaњa пoљoпpивpeдним oкpyжeњeм зa кojи ce знa дa je oд кopиcти oпpaшивaчимa, мaдa je cвeгa нeкoликo њиx тo ypaдилo дa би пoдcтaкли oпpaшивaчe. Пчeлapи cy били нeoдлyчни пpeмa мнoгим мacoвнo цвeтajyћим биљкaмa, пpи чeмy cy нeки пчeлapи кopиcтили тe биљкe зa пpoизвoдњy мeдa, дoк cy иx дpyги избeгaвaли збoг yoчeниx pизикa oд пecтицидa. Peзyлтaти oткpивajy бpojнe пpeвиђeнe нeдocтaткe y знaњy кoje ћe yтицaти нa paзмeнy знaњa и capaдњy измeђy двe гpyпe. Izvleček: Opraševanje z žuželkami je ključno za številne kmetijske rastline, pogosto z najetimi čebeljimi družinami za namen opraševanja. Kljub obsežnim raziskavam upravljanja opraševanja še nobena evropska raziskava še ni proučila, kako in zakaj kmetje upravljajo z opraševalskimi storitvami. Malo jih je tudi raziskalo, zakaj čebelarji uporabljajo določene kmetijske rastline. Z anketiranjem čebelarjev in kmetov v 10 evropskih državah je ta raziskava proučila dojemanje in motivacijo čebelarjev in kmetov glede opraševanja kmetijskih rastlin. Skoraj polovica anketiranih kmetov je verjela, da je pomanjkljivo oprašena ena ali več njihovih kmetijskih rastlin. Manj kot tretjina kmetov je najela opraševalske storitve. Je pa večina vključenih v vsaj eno obliko kmetijsko‐okoljskih ukrepov, za katero je znano, da koristijo opraševalcem, čeprav le redki z namenom pomoči opraševalcem. Odnos čebelarjev do masovno cvetočih kmetijskih rastlin je bil ambivalenten. Nekateri jih uporabljajo za pašo čebel, drugi pa se jim zaradi tveganja v zvezi pesticidi izogibajo. Ugotovitve osvetljujejo številne spregledane vrzeli v znanju, ki bodo vplivale na izmenjavo znanja in sodelovanje med obema skupinama.